The study of English Language as Lingua Franca in Pakistan (British Journal of Multidisciplinary and Advanced Studies, 2023)
This research aims to study the English language as a Lingua Franca in Pakistan. The focus area of this research is to study English language perception, future perspective, current academic, and advantages and disadvantages of a language. The theoretical framework of Language power (2005) by Houston. There are two components of Language power: 1) Ability to speak and understood, 2) Ability to listen and understand. Progression through the stages is aimed at the understanding of the English language. How this language is taking place in the Pakistan educational system. The representation of this research will contribute to the future of the English Language in Pakistan and Pakistan soon to be a small English valley.